SHARIA BASED TOTAL QUALITY MANAGEMENT FRAMEWORK IN ISLAMIC EDUCATIONAL INSTITUTIONS THE DELPHI METHOD APPROACH - Norman, Efrita; Arie Pratama, Fidya; Paramansyah, Arman; Feviasari , Heni; Vikaliana, Resista (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study addresses the integration of Sharia-based principles into Total Quality Management (TQM) frameworks within Islamic educational institutions, aimed at enhancing management quality while upholding Islamic ethical standards. The purpose of this research is to develop a comprehensive TQM framework that aligns with Sharia values to promote moral accountability, fairness, and stakeholder satisfaction. Utilizing the Delphi method, the study gathers consensus from experts in Islamic education and TQM to establish a well-defined, contextually relevant framework. The research involved several rounds of expert surveys, focusing on key TQM components such as transparency, continuous improvement, and ethical leadership in an Islamic context. Principal findings reveal that incorporating Sharia principles in TQM fosters a balanced approach, merging academic excellence with spiritual and moral development. The developed framework underscores the importance of fairness, ethical governance, and stakeholder engagement, positioning Islamic educational institutions to address contemporary challenges while maintaining their religious identity. This study contributes a novel framework that not only strengthens the administrative and educational aspects but also ensures alignment with Sharia values, thereby offering a robust model for quality management in Islamic education.